Crossing The Gap Between Stakeholders: Qualitative Study of Stakeholders’ Perspective on Adolescent Health Program in Surabaya - Muthmainnah, Muthmainnah; Nurmala, Ira; Agus Salim, Lutfi; Puspita Devi, Yuli; Ying Lin, Chung; Yulia Restuti, Dini; Laverack, Glenn (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Nearly 30% of Indonesian population is adolescent. Indonesia has various programs to improve the health status of adolescents from various sectors. However, the program intended for adolescent reproductive health has not been fully utilized, with one of the reasons being improper management by primary healthcare on cross-sector cooperation causing a knowledge gap among adolescents about the program. Purpose: This study aims to identify the perception of stakeholders from various sectors on adolescent health program in Surabaya, East Java. Methods: This study used a qualitative descriptive approach through interviews and FGDs to relevant stakeholders. Research subjects came from elements of government (health, education, religion, family planning, and social), NGOs, media (radio, newspaper media), teachers (representatives of 10 high schools in Surabaya), parents (Family Health Empowerment group). Data were analyzed by thematic analysis. Results: Every governmental office has a program for adolescents, but most are only providing information. Therefore, NGOs complete programs have not been implemented by the government such as a peer educator program for high-risk community. The media also has youth programs that are tailored to the needs or trends. Teachers and parents as having the closest control with adolescents, also play a role in providing information and accompanying adolescents. The various roles of the various stakeholder groups require synergy efforts to avoid overlapping. Conclusion: Adolescents in Surabaya are considered unhealthy and engage in risky behaviors by relevant stakeholders. Various programs have been implemented to support adolescent health. However, different perspectives on implementing adolescent health programs can cause conflict between stakeholders or confusion among adolescents. The diversity of stakeholders involved in adolescent health programs also needs to be encouraged.